2007
DOI: 10.2741/2368
|View full text |Cite
|
Sign up to set email alerts
|

Wnt pathway and breast cancer

Abstract: Breast cancer is one of the most debilitating human carcinomas with second highest mortality rate after lung cancer in women. Recent advancement in genetic and biochemical analyses has deciphered the molecular pathways involved in breast cancer development. Wnt signal has long been established to play a critical role in normal development as well as in tumorigenesis. In this review, we summarize the role of Wnt signal in the development of mammary carcinoma, the molecular mechanism via which Wnt signal exerts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 145 publications
2
41
0
Order By: Relevance
“…Interestingly, of those genes with evidence for clinical relevance, Wnt pathway alterations (eg, WNT5A, VANGL1, WISP1) are particularly predominant in the comparison between 21PTci and 21NTci (representing the ADH to DCIS transition). This is consistent with recent studies implicating both the canonical and noncanonical Wnt-signaling pathways in initiation and maintenance of breast tumorigenesis (reviewed in Mohinta et al 61 ) as well as in cancer stem cell self renewal and the initiation of the epithelial to mesenchymal transition. 62 In particular, the planar cell polarity (PCP) pathway (a non-canonical Wnt pathway), involving ligand WNT5A, has been said to have either inhibitory or promoting roles in various cancers, depending on the context (reviewed in Kikuchi and Yamamoto 63 ).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, of those genes with evidence for clinical relevance, Wnt pathway alterations (eg, WNT5A, VANGL1, WISP1) are particularly predominant in the comparison between 21PTci and 21NTci (representing the ADH to DCIS transition). This is consistent with recent studies implicating both the canonical and noncanonical Wnt-signaling pathways in initiation and maintenance of breast tumorigenesis (reviewed in Mohinta et al 61 ) as well as in cancer stem cell self renewal and the initiation of the epithelial to mesenchymal transition. 62 In particular, the planar cell polarity (PCP) pathway (a non-canonical Wnt pathway), involving ligand WNT5A, has been said to have either inhibitory or promoting roles in various cancers, depending on the context (reviewed in Kikuchi and Yamamoto 63 ).…”
Section: Discussionsupporting
confidence: 93%
“…Wnt signaling has been implicated in several human tumors, among which are skin, connective tissue, colon, gastric, lung, breast, and prostate (3)(4)(5)(6)(7)(8)(9). In addition, recent studies highlighted the potential role for Wnt signaling in STS.…”
Section: Introductionmentioning
confidence: 99%
“…1 Despite advances in genetic and biochemical analyses, which have deciphered many specific molecular signatures, a deeper molecular basis of transformation is still unknown in this tumor. [2][3][4][5] Recently, an increasing body of evidence has shown that deregulation of miRNAs is associated with cancer development.…”
Section: Introductionmentioning
confidence: 99%